The last verse : a novel - Frost, Caroline (William Morrow, an imprint of HarperCollins Publishers, 2024)
From the author of the award-winning Shadows of Pecan Hollow comes a novel set in the country music world of 1970s Nashville about a struggling musician who writes a hit song that both promises her long-sought-after fame and implicates her in a heinous crime.